IMPORTANT DETERMINANT TERRITORIAL ORGANIZATION OF THE HOTEL INDUSTRY IN LVIV REGION IS URBANIZATION - Ганич, Н. М. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
The aim of this article is to analyze the features of the territorial organization of the hotel industry in L’viv Region with the impact of such factor as urbanization. Territorial organization of the hotel industry is dependent on the systems of settling.This article explores the impact of urbanization on the territorial organization of the hotel industry attractive for tourism in Lviv region. Application one of mathematical methods in the study confirms the direct impact of the territorial concentration of population in cities on the location of accommodation facilities. However, the observed impact of urbanization and poor geography companies hotel industry in major cities and peripheral districts.The places with the biggest demand for the accommodation services are big cities and recreational-tourist destinations. The tendencies of the allocation of the hotel complexes are highlighted. Functions of the hotels greatly influence their allocation in the planning structure of the city.As the result of the conducted centro-graphic analysis the inter-impact of the urbanization level and geography of the accommodation sites was revealed. In L’viv region the mono-centric L’viv agglomeration was formed and multi-centric Drohobych and Truskavets agglomeration is being formed.The rational allocation of the chain of hotels provides comfort for people and enhance the effectiveness of the enterprises.